RE-ECHO: METABOLIC SYNDROMA SCREENING PROGRAM AND LOW-INFLAMMATION DIET EDUCATION - Simarmata, Mesrida; Srininta; Sinta, Dinda Sitorus Grace; Rahma, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background :​ Syndrome metabolic is gathering risk disease cardio vascular , diabetes mellitus and stroke syndrome metabolic This can occurs in adolescents , adults and the elderly . Metabolic syndrome in mothers pregnant can result in fetal disorders​ even childhood obesity .​ Hence the syndrome metabolic This can happen everywhere age . Methods: Study quantitative , pre experiment , with design one group pretest and posttest design . Population : parents PAB 8 Saentis High School students . Sample: Engineering taking sample is accidental sampling. Parents students who come to place research that is wanted become respondents study as many as 45 people. Instruments research : sheet observation results metabolic screening : Blood pressure, blood sugar levels glucose blood , levels sour urate ( purine) blood ). Questionnaire sheet For measure knowledge respondents on an anti- inflammatory diet . Data were analyzed using the Wilcoxon test for mean differences with P value P<0.05 then There is difference knowledge before and after low-fat diet education inflammation . Results: Screening results : Majority age respondents aged risky in reproduce that is age > 35 years as many as 39 people (86.7%) glucose levels blood the majority were normal , as many as 43 people ( 95.6%), the level purine in respondents is majority normal as many as 24 people (53.3%). bring score knowledge before education min - max 30-80, mean 52.78 and score knowledge after Education min- max 40-90 mean 73.33. Mean difference test The Wilcoxon test value obtained P value 0.000 (P < 0.05 ) There is difference knowledge respondents before with after given education syndrome metabolic and low diet inflammation . Conclusions: education about syndrome metabolic and inflamation low in effective respondents increase knowledge respondents